In vitro activity of copper(II) complexes, loaded or unloaded into a nanostructured lipid system, against mycobacterium tuberculosis - da Silva, Patricia B. [UNESP]; de Souza, Paula C. [UNESP]; Calixto, Giovana Maria Fioramonti [UNESP]; Lopes, Erica de O. [UNESP]; Frem, Regina C. G. [UNESP]; Netto, Adelino V. G. [UNESP]; Mauro, Antonio E. [UNESP]; Pavan, Fernando R. [UNESP]; Chorilli, Marlus [UNESP] (MDPI, 2016)
Tuberculosis (TB) is an infectious disease caused mainly by the bacillus Mycobacterium tuberculosis (Mtb), presenting 9.5 million new cases and 1.5 million deaths in 2014. The aim of this study was to evaluate a nanostructured lipid system (NLS) composed of 10% phase oil (cholesterol), 10% surfactant (soy phosphatidylcholine, sodium oleate), and Eumulgin® HRE 40 ([castor oil polyoxyl-40-hydrogenated] in a proportion of 3:6:8), and an 80% aqueous phase (phosphate buffer pH = 7.4) as a tactic to enhance the in vitro anti-Mtb activity of the copper(II) complexes [CuCl2(INH)2] H2O (1), [Cu(NCS)2(INH)2]5H2O (2) and [Cu(NCO)2(INH)2]4H2O (3). The Cu(II) complex-loaded NLS displayed sizes ranging from 169.5 ± 0.7095 to 211.1 ± 0.8963 nm, polydispersity index (PDI) varying from 0.135 ± 0.0130 to 0.236 ± 0.00100, and zeta potential ranging from -0.00690 ± 0.0896 to 8.43 ± 1.63 mV. Rheological analysis showed that the formulations behave as non-Newtonian fluids of the pseudoplastic and viscoelastic type. Antimycobacterial activities of the free complexes and NLS-loaded complexes against Mtb H37Rv ATCC 27294 were evaluated by the REMA methodology, and the selectivity index (SI) was calculated using the cytotoxicity index (IC50) against Vero (ATCC® CCL-81), J774A.1 (ATCC® TIB-67), and MRC-5 (ATCC® CCL-171) cell lines. The data suggest that the incorporation of the complexes into NLS improved the inhibitory action against Mtb by 52-, 27-, and 4.7-fold and the SI values by 173-, 43-, and 7-fold for the compounds 1, 2 and 3, respectively. The incorporation of the complexes 1, 2 and 3 into the NLS also resulted in a significant decrease of toxicity towards an alternative model (Artemia salina L.). These findings suggest that the NLS may be considered as a platform for incorporation of metallic complexes aimed at the treatment of TB.
Keywords: Artemia salina L; Copper(II) complexes; Cytotoxicity; Mycobacterium tuberculosis; Nanostructured lipid system; Tuberculosis